Fostering Students’ Mental Health in a Covid- 19 Era: E- Counselling, Paradigm Shift and Issues of Policy - Enokela, Abel; Aluede, Oyaziwo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
This effort theoretically examined the effects of the Covid-19 pandemic on students’ mental health. It evaluated the roles of school-based counselors in providing mental health services to them through e-counseling since the ongoing pandemic requires physical distancing as a means of controlling the spread of Coronavirus.  Psychological disturbances among students are expected to be high due to the psychosocial disruptions produced by prolongs isolation, and other challenges attributable to the pandemic. Professionals in various disciplines have adopted e-platforms to carry out their activities. Thus, this effort sought to engage counselors with the necessity of embracing e-therapy to foster students’ mental wellbeing. Thus, the essentiality of a paradigm shift from conventional counseling to online counselling cannot be overstressed; issues of policy in the administration of guidance and counseling in a Covid-19 era are crucial. Therefore, the need to put in place policy guidelines for online counseling to enhance effective delivery of counseling services with ethical values in view cannot be overemphasized. It is hereby recommended, among others, that counseling bodies worldwide need to rub minds to share knowledge and skills on how to reposition counseling to meet the emerging and peculiar counseling needs of students.